The impact of event tourism on tourism facilities operating in Azerbaijan - Hasanov, Hikmat (Management and Entrepreneurship: Trends of Development, 2024)
The purpose of the study - The impact of event tourism on tourism facilities operating in Azerbaijan is a multifaceted topic. An event involving events such as sporting, cultural or business gatherings can have a significant impact on local tourism facilities. Some potential impacts include: Hotels, hostels and other accommodation facilities may experience increased demand during major events, leading to increased occupancy rates and potentially higher prices. Restaurants, cafes and bars may see an increase in customers, especially those located near event venues. Event tourism can put pressure on local transport systems. Improved infrastructure may be needed to handle increased tourist traffic. Local culture can be both showcased and influenced by event tourism.It can lead to a greater appreciation of local heritage and traditions. On the downside, there may be pressures on the environment due to increased waste and resource use. Socially, there may be disruptions to the daily life of the local community. New tourism facilities, including hotels, entertainment venues and cultural facilities, may be developed in anticipation of or in response to event tourism.Applied significance of the study- The study can inform government and local authorities in creating effective policies and strategies to manage and maximize the benefits of event tourism. Insights from the research can guide the development of sustainable tourism practices, ensuring that event tourism does not harm local environments or communities. Understanding the economic impacts of event tourism helps with budgeting, financial planning and investment in tourism infrastructure. Research can highlight ways in which local communities can engage and benefit from event tourism and ensure that it supports inclusive development.The results of the study are likely to provide valuable insights in several key areas:Economic Impact Analysis: This includes information on revenue generation, employment rates in the tourism sector and overall contribution to the local and national economy.Infrastructure and Facility Use: Findings on how event tourism affects the use and development of tourism facilities, including hotels, transportation and entertainment venues.Environmental impacts: It is possible to observe both positive and negative environmental consequences of increased tourism activity.Socio-cultural impacts: Insights into how event tourism affects local communities, culture and heritage, including positive aspects such as cultural exchange and potential negative impacts such as cultural commodification.Tourist Behavior and Preferences: Information on tourist demographics, spending patterns, preferences and satisfaction levels.Originality and scientific innovation of research can be characterized by several unique aspects. Studying the unique context of Azerbaijan with its distinct culture, geography and socio-economic background adds original value to the global understanding of event tourism. An inclusive approach that considers economic, environmental, social and cultural dimensions provides a holistic understanding that is uncommon in more narrowly focused studies. Including the views and experiences of local communities, businesses and authorities in Azerbaijan can reveal insights that are overlooked in more tourist-focused research. Using innovative research methodologies or data analysis techniques contributes to the originality of the research. Bridging different academic disciplines such as tourism studies, economics, sociology and environmental science can provide a new perspective. JEL Classification: L8, L83